Salp swarm algorithm‐based fractional‐order PID controller for LFC systems in the presence of delayed EV aggregators. Issue 3 (1st September 2020) - Babaei, Farshad; Lashkari, Zahra Bahari; Safari, Amin; Farrokhifar, Meisam; Salehi, Javad
Abstract : Electric vehicles (EVs) battery has the ability to enhance the balance between the load demand and power generation units. Random behaviour of owners and EVs low capacity are some factors that develop the EV aggregator notion to increase the EV participation in the ancillary services market. In the presence of EVs aggregator, the frequency control service is capable of causing time‐varying delay in load frequency control (LFC) systems. Owing to the dependency of controller effectiveness on its parameters, these parameters should be designed optimally in order to have a better result in an LFC system in the presence of time‐varying delay. Therefore, a salp swarm algorithm (SSA) is utilised to adjust the fractional‐order proportional integral derivative (PID) (FOPID) controller coefficients. Also, some evaluations are performed about the proposed LFC performance by an integral absolute error, integral time absolute error and mean absolute error indicators. In this study, both single and two‐area LFC systems containing EVs aggregator with time‐varying delay are simulated and analysed. The results indicate that the proposed controller has fewer frequency variations in contrast to other controllers presented in the case studies. Moreover, it is concluded that the FOPID controller could significantly decrease the overshoot and settling time of the frequency variation signal.